Tunable Platform Capacity of Metal–Organic Frameworks via High-Entropy Strategy for Ultra-Fast Sodium Storage - Shusheng Tao; Ziwei Cao; Xuhuan Xiao; Zirui Song; Dengyi Xiong; Ye Tian; Wentao Deng; Youcai Liu; Hongshuai Hou; Guoqiang Zou; Xiaobo Ji (Nano-Micro Letters)
Highlights A novel high-entropy metal–organic frameworks (HE-MOFs) electrode for fast sodium-ion storage devices has been realized by introducing five metallic elements. The platform capacity/voltage of the electrode materials are precisely regulated by the adjustable metal species/content of HE-MOFs. The sodium-ion capacitors assembled based on high-entropy MOFs electrode exhibit high-power density (20,000 W kg-1) and high-energy density (99.4 Wh kg-1).